Discrete Event Simulation in the Health Policy and Management Program - Groothuis, S.; Merode, van G. G. (Methods of Information in Medicine, 2000)
Students in Health Policy and Management at the Faculty of Health Sciences of Maastricht University must learn to analyze and design workflow processes in health care. To attain this, a discrete event simulation training, using MedModel™ is used. This paper describes the training in two consecutive years. In both years the training was evaluated systematically. The evaluation results demonstrate that the simulation training increased the students’ knowledge about analyzing and designing workflow processes in healthcare. Students considered the training as a very important part of their program.
Keywords: Discrete Event Simulation; Education; Health Sciences; Management; Evaluation